P18 The effects of acute and repeated bouts of unilateral Neuromuscular Electrical Stimulation on quadriceps muscle inflammation in COPD. (12th November 2015) - Gray, A; Latimer, L; Parmar, A; Bradding, P; Greening, NJ; Steiner, MC
Abstract : Introduction and objectives: Impaired skeletal muscle function is an important systemic manifestation of COPD which can be improved by exercise training. Non-volitional training using neuromuscular electrical stimulation (NMES) may be an effective training technique in situations where voluntary exercise may be difficult or impractical (e.g. peri-exacerbation or severe ventilatory limitation). Exercise is known to result in both intramuscular and systemic inflammation. However, the cellular response to NMES, which directly depolarises the motor units, is unclear. We investigated the impact of acute and repeated bouts of unilateral NMES in COPD patients. Methods: 16 patients underwent 6 weeks of unilateral NMES 5 times a week for 30 min at 50 Hz at Glenfield Hospital, Leicester. Mean (SD) age was 65 (9) years, FEV1 : 50 (22)% predicted, BMI 26.5 (5.2) Kg/m 2 ). Isometric quadriceps strength, regional muscle mass (DEXA) and quadriceps thickness (ultrasound) were recorded at baseline and at the end of the intervention. Vastus lateralis muscle biopsies were obtained from both the trained and untrained limbs at baseline, 24 h after the first bout of NMES and at 6 weeks. Venous blood was taken at the same time. Biopsies were analysed for neutrophil (neutrophil elastase) and macrophage (CD163) density using immunohistochemistry. ELISA measurements of inflammatory cytokines (IL-6 and TNFα) were performed on blood samples. Results: Quadriceps strength increased by 7.6% (p = 0.024), thigh mass by 2.8% (p = 0.185), and quadriceps thickness by 11% (p = 0.002). Muscle biopsies for 11 patients were analysed. Neutrophil density 24 h after a single bout of unilateral NMES significantly increased in both the trained and untrained limb, with larger increase in the stimulated muscle (Table 1 ). Neutrophil density returned to baseline in the trained limb following training. No changes were seen in muscle macrophage density, serum IL-6 or serum TNFα. Conclusion: A single bout of unilateral NMES provokes an intramuscular neutrophilic inflammatory response in both the trained and untrained limb, which are not mediated by changes in circulating IL-6 or TNFα. Neutrophil infiltration returned to baseline in the stimulated leg following training.